Sort Mii Out: Learning to Value Portable Gaming Encounters Through Nintendo's Streetpass Software. Issue 6 (September 2018) - Moore, Kyle
Released in 2011, the Nintendo 3DS is the next generation of portal consoles from Japanese gaming company Nintendo. Following the success of the Nintendo DS (Dual Screen), the new console brings with it three-dimensional stereoscopic graphics and the new social software Streetpass . This article adopts a situated approach in order to explore the significance of Streetpass in mediating social encounters within material environments. This article suggests that this software follows a history of mediating encounters through portal consoles, resulting in a training of players to view encounters within a software-sorted logic of value.